CIED malfunction in patients receiving radiation is a rare event that could be detected by remote monitoring. (22nd June 2018) - Bravo‐Jaimes, Katia; Samala, Vikram; Fernandez, Genaro; Moravan, Michael J.; Dhakal, Sughosh; Shah, Abrar H.; Messing, Susan; Singh, Kyra; Aktas, Mehmet K.
Abstract: Introduction: An increasing number of patients with cardiac devices require radiation therapy for treatment of a variety of cancers. This study aimed to identify the incidence and predictors of cardiac implantable electronic devices (CIED) malfunction in a real‐world population that has received radiation therapy. Methods: This retrospective cohort study included 109 adult patients who received radiation therapy at the University of Rochester Medical Center, Radiation Oncology Department, between 2000 and 2015. Sixty patients had pacemakers and 49 had automatic implantable cardioverter defibrillators. Subjects received either high energy (16 MV) and/or low energy (6 MV) photon beams with or without electron beams (6–16 MeV). We included interrogations done from first day of radiation and up to 3 months' postradiation therapy. Outcomes analyzed were device‐related malfunctions and device‐related clinical events. Fisher's exact, Wilcoxon, and Kruskall‐Wallis tests were used for bivariate analysis. Logistic regression with robust adjustment was used for multivariate analysis. Results: We identified six device‐related malfunctions. All events were minor and included partial settings reset leading to loss of historical data, pacing thresholds changes, lead impedance changes, and LV output increase. Two patients had device‐related clinical events, including dyspnea and diaphragmatic‐stimulation. In bivariate analysis, CIED malfunction was associated with CIED duration in situ . In multivariate analysis, there was no significant statistical association between adverse events and beam energy type, CIED location, or dose of radiation delivered to the target. Conclusions: CIED malfunctions are uncommon in real‐world patients and associated with minor clinical events. In our cohort, remote CIED monitoring would have identified all events.